From stretch to deflection: the importance of context in the activation of mammalian, mechanically activated ion channels. (17th June 2021) - Richardson, Jessica; Kotevski, Adrian; Poole, Kate
Abstract : The ability of cells to convert mechanical perturbations into biochemical information is an essential aspect of mammalian physiology. The molecules that mediate such mechanotransduction include mechanically activated ion channels, which directly convert mechanical inputs into electrochemical signals. The unifying feature of these channels is that their open probability increases with the application of a mechanical input. However, the structure, activation profile and sensitivity of distinct mechanically activated ion channels vary from channel to channel. In this review, we discuss how ionic currents can be mechanically evoked and monitored in vitro, and describe the distinct activation profiles displayed by a range of mammalian channels. In addition, we discuss the various mechanisms by which the best‐characterized mammalian, mechanically activated ion channel, PIEZO1, can be modulated. The diversity of activation and modulation of these mammalian ion channels suggest that these molecules may facilitate a finely controlled and diverse ability to sense mechanical inputs in mammalian cells. Abstract : Mechanically activated ion channels mediate the conversion of mechanical inputs into electrochemical signals. Evidence suggests that different mechanically activated ion channels display distinct activation profiles in response to membrane stretch, cellular indentation and deflections applied at the cell–substrate interface. These channels are also modulated by features and molecules found within distinct cellular compartments. It is therefore vital to consider the mechanical and cellular context surrounding channels to understand their function.